(untitled) (Modern education and development, 2025)
The lexeme "fashion blog" has emerged as a prominent term within digital and cultural discourse, encapsulating both the lexical evolution of the fashion industry and the digitalization of personal narratives. This article explores the linguistic structure, semantic properties, morphological composition, and sociolinguistic relevance of the lexeme "fashion blog." Drawing upon modern linguistic theories and discourse analysis, the study investigates how the combination of two distinct lexical items creates a new, culturally loaded unit of meaning. The research further delves into its usage in different contexts, its frequency in media, and its implication in shaping modern language use. Additionally, the study compares this lexeme to similar digital culture-related terms to highlight broader trends in lexical innovation and socio-discursive shifts.